Ultrasound treatment on saffron (Crocus sativus L.) corm: Impact on textural, morphological, and microbial properties and stigma- derived metabolite compositions - Bibi Marzieh Razavizadeh; Seyed Mahdi Ziaratnia (Heliyon)
This research aimed to assess the influence of ultrasound at a frequency of 37 kHz on various parameters of saffron (Crocus sativus L.) plants, including flowering efficiency, morphological, and textural properties, corm surface microbial population, and the concentrations of key secondary metabolites in saffron stigmas. Ultrasound was applied to saffron corms during two distinct growth stages, namely flower induction and flower initiation, utilizing varying sonication durations (0, 15, 30, and 60 min). Notably, flowering efficiency experienced a significant decrease (P ≤ 0.05) after 60 min of sonication compared to the control at both stages. In contrast, an increase in sonication time from 0 (control) to 15 and 30 min resulted in a noteworthy augmentation in the number of flowers and flowering efficiency. The structural morphology of corms did not exhibit significant alterations under ultrasound at different durations within each stage. Extended exposure time showed efficacy in diminishing microbial population on corm surfaces and reinforcing corm resistance against compressive forces. High-performance liquid chromatography (HPLC) analysis of saffron stigmas revealed that a significant increase in crocin content compared to the control at both stages, a trend that persisted with increasing sonication time up to 60 min. However, picrocrocin and safranal contents exhibited a decrease in both stages with prolonged sonication. These findings imply that ultrasound not only impacts the flowering efficiency of saffron corms but also exerts an influence the concentrations of secondary metabolites in the resultant stigma.